Production of Silver Nanoparticle Chains inside Single Wall Carbon Nanotube with a Simple Liquid Phase Adsorption - Alimin Alimin; Narsito Narsito; Indriana Kartini; Sri J. Santosa (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
This article described a successful growing of silver nanoparticle chains (AgNPs) within the internal spaces of single wall carbon nanotube (SWCNT). The use of ethanol in the liquid phase adsorption could produce relatively long silver nanoparticle chains encapsulated in the nanotubes (AgNPs-SWCNT). A significant decrease of nitrogen uptake and radial breathing mode (RBM) as well as tan-gential mode (G band) upshifts of AgNPs-SWCNT specimen suggest that the nanoparticles have been encapsulated in the internal tube spaces of the nanotube. The presence of metallic silvers on the exter-nal surface of the carbon nanotube that was observed by scanning electron microscope and examined by X-ray diffraction technique was successfully able to be removed by ultrasonic using 1 M HNO3. The remaining small residue obtained after thermal gravimetric analysis up to 1100 K supports the sugges-tion on the presence of silver encapsulated inside SWCNT. Copyright © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).